Influence of Fine Management Combined With PDCA Cycle Method on Disinfection Qualified Rate and Performance Grade of Ophthalmic Precision Instruments - Zeng, Fanli; Wang, Xiuling; Gao, Yan; Hu, Ling (Frontiers in Surgery, 2022)
Objective:To explore the influence of fine management combined with plan-do-check-action (PDCA) cycle method on the management of ophthalmic precision instruments. Methods: The ophthalmic precision instruments centralized in the disinfection supply room of our hospital were selected as the research object, and divided into group A and group B. Traditional instrument management method was adopted in group A, fine management combined with PDCA cycle method on the basis of group A was adopted in group B. The instruments management risk scores, qualified rate of disinfection, instruments performance grade, incidence of toxic anterior segment syndrome (TASS) of two groups were compared. Results:The risk scores of instruments management, incidence of TASS in group B were lower than those in group A (P<0.05). The qualified rate of disinfection, instruments performance grade in group B were higher than those in group A (P<0.05). Conclusion:Fine management combined with PDCA cycle method can improve the qualified rate of disinfection of ophthalmic precision instruments, optimize the performance of instruments, reduce the risk of instrument management and reduce the incidence of TASS.